Upaya Guru Pendidikan Agama Kristen dalam Membentuk Karakter Jujur dan Bertanggung Jawab pada Siswa - Yuel, Yuel; Nina, Nina (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims todescribe the efforts of Christian Religious Education teachers in instillinghonesty and responsibility in students of class X TKR A at SMK Karsa MulyaPalangka Raya. Character education is very important, especially in today'schallenging and changing times. Character education is also equally importantin vocational education for the future and the world of work. This studyused a qualitative approach with a case study method. Data was collectedthrough direct observation, interviews, and document collection. The results of thestudy show that PAK teachers actively teach the values of honesty andresponsibility through classroom lessons, set a good example in theirdaily attitudes, and provide direct guidance and encouragement to students. Teachersalso invite students to participate in practical activities and discussions so that they betterunderstand and can apply the values of honesty and responsibility intheir daily lives. This process is aided by support from theschool and family environment, as well as the teachers' friendly and approachable manner towards students. However,there are also obstacles such as the influence of the environment outside of school and a lack ofawareness from the students themselves.